Some further experiments in fatigue testing at 20 kH2 - Hockenhull, B. S. (College of Aeronautics, 1968)
Considerations are made of the suitability of acoustic transformers applied to fatigue testing at 20 kH2. A suitable system has been constructed which allows the use of plain cylindrical specimens. The results of fatigue tests on an aluminium alloy are given and discussed in relation to structure and environment.